A recommended exercise program appropriate for patients with knee osteoarthritis: A systematic review and meta-analysis - Guo, Xuanhui; Zhao, Peng; Zhou, Xiao; Wang, Jialin; Wang, Ruirui (Frontiers in Physiology, 2022)
Background: Knee osteoarthritis (KOA) is a common degenerative disease. Recommended first-line management includes exercise. However, there is still no standard recommendation for the appropriate exercise program for patients with KOA. Purpose: To compare the effects of a land-based exercise program with high vs uncertain compliance with recommendations among people with KOA in pain, function, and stiffness. Methods: From January 2000 to January 2022, PubMed, EBSCO, Sport-discuss, Medline, and Web of Science were searched. A comprehensive review of meta-analyses of land-based exercise programs with exercise prescription was done in symptomatic individuals with KOA. The Cochrane Collaboration's standards were followed for study selection, eligibility criteria, data extraction, and statistics, and the Cochrane Collaboration's tool was used to assess the risk of bias. Review Manager 5 software was used to extract the baseline mean and follow-up value, as well as the accompanying standard deviation, to calculate the Standardized Mean Difference (SMD). In meta-analyses, SMD was calculated for pain outcomes, self-reported physical function, and stiffness. The effects of the outcome on the subgroups of studies were compared. A fixed or random effects model was used in group research with comparable outcomes. Results: There were fifteen studies with a total of 1436 participants. Compliance with the ACSM recommendations was categorised as "high" in five cases and "uncertain" in nine others. The SMD for pain was -0.31 (95% CI -0.47, -0.14) in the subgroup with a high ACSM compliance ratio and -0.55 (95% CI -0.69, -0.41) in the subgroup with uncertain ACSM compliance. For physical function, in the high-compliance group, the SMD was -0.21 (95% CI -0.38, -0.05), while in the uncertain compliance group, it was -0.61 (95 % CI -0.82, -0.40). The SMD was -0.40 (95 % CI -0.61, -0.19) for stiffness and high compliance with ACSM. The SMD was -0.29 (95% CI -0.66, 0.07) for study interventions with uncertain compliance. Conclusion: The results showed that the land-based training program significantly improved pain, physical function, and stiffness in KOA patients compared to controls. Exercise interventions with high adherence to ACSM recommendations differed significantly only in stiffness measures compared with the uncertain compliance group.